Telemedicine: A Natural Evolution of Obstetric and Gynaelogical health Care System of Bangladesh during COVID-19 Pandemic - Banik, Mala (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: The word Telemedicine literally translates to ‘healing at a distance’. Here remote diagnosis and treatment of patients is done by means of telecommunication technology. First published record of telemedicine is in the first half of the 20th century when ECG was transmitted over the telephone line. In Bangladesh telemedicine was not so popular as patients prefer face to face visit to a medical practitioner. But in Covid-19 Pandemic to prevent transmission and Lock down situation telemedicine becomes popular and emerges as a natural evolution of Obstetrics and Gynaecologic health care system in Bangladesh. The Aim of the study: To see the outcome of patients taking telemedicine for their Obstetric and Gynaecologic problems. The reasons of seeking consultation through telemedicine are also studied. Materials and Methods: This is a Cross sectional prospective study done during Lock down period in Bangladesh. Study period was 27th March to 20th May. Total 201 women got telemedicine service free of cost via sms, messenger, imo, whatsapp, email using smart phone were included in this study. The data was collected, edited and tabulated by hand tabulation. Calculation was done on scientific calculator. Results: About 96.51% patients suffering from Obstetrics and Gynaecological diseases were cured by taking medicine, counselling and assurance through telemedicine. Majority of pregnant women(23.88%) sought telemedicine service for consultation about advice regarding diet, medicine, anxiety about ANC visits. 2.48% women were worried about Tetanus Toxoid vaccine.Women (.99%) suffering from Gynaecological diseases such as Fibroid uterus, Uterine Prolapse were seeking for operation.3.48% women suffereing from DUB and managed by medication . Only 3.48% patients were required to refer to Hospital for Emergency admission. Conclusion: Telemedicine can’t give solution to all problems, but it definitely helps in managing women suffering from Obstetric and Gynaecological diseases at a large extent especially during awakward situation like Covid 19 pandemic. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 23-27